PENGARUH PENGGUNAAN MEDIA GAMBAR PAPAN FLANEL TERHADAP KEMAMPUAN MEMBACA ANAK DISLEKSIA (ABK) PADA PEMBELAJARAN TEMATIK - Siti Widiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problem in this research is whether using flannel board drawing media can influence the reading ability of dyslexic children in class III of SD Negeri 18 Sembawa in thematic learning. The aim of this research is to improve the reading ability of dyslexic children in thematic learning. This research is experimental research. The method used is pre-experimental design. The design of this research is one group pre-test and post-test design. This research sample uses purposive sampling. From the results of the hypothesis test or t test, the calculated t is obtained, namely with a significance value < 0.05, with a sig value of 0.000 < 0.05, the results of the homogeneity test carried out are 0.580 > 0.05, so it can be concluded that the data is homogeneous. So it can be concluded that "There is an influence on the use of flannel board drawing media on the reading ability of dyslexic children in temetic learning"